X-ray analysis of some shape memory CuZnAl alloys due to the cooling rate effect - Eskil, M; Kayali, N (Elsevier Science Bv, 2006)
Copper-based shape memory alloys are very sensitive to the thermal effects before and after the transformation, and these effects may cause important changes on crystallographic properties or the other transformation parameters of the alloys. In this study, the changes which occurred on some transformation parameters of two shape memory CuZnAl alloys due to the effects of various thermal procedures have been investigated by using X-ray diffraction. At the specimens cooled from high temperature p phase region, the L2(1)-> M18R martensitic transformation was observed. The lattice parameters of M18R monoclinic martensitic structure, tetragonality (psi) and the changes occurred by cooling rate on lattice parameters were defined. In addition, spacing differences (Ad) between some selected pairs of diffraction planes with (h(1)k(1)l) ve (h(2)k(2)l) Miller indices 2 satisfying the relation (h2/1-h2/2)/3=(k2/2-k2/1)/n (n= 1 for 9R and n=4 for 18 R structure) were examined due to the cooling conditions. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: CuZnAl alloys; shape memory effect; M18R martensitic structure; cooling rate effects; interplanes distance difference